1996
DOI: 10.1016/0014-5793(96)00280-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of permeability transition interfere with the disruption of the mitochondrial transmembrane potential during apoptosis

Abstract: In a number of experimental systems, the early stage of the apoptotic process, i.e. the stage which precedes nuclear disintegration, is characterized by the breakdown of the inner mitochondrial transmembrane potential (AWm). Here we address the question as to whether mitochondrial permeability transition (PT) pores may account for the A~IJ m dissipation in lymphocyte apoptosis. Drugs known for their PT-inhibitory potential (hongkrekic acid, cyclosporin A, and the non-immunosuppressive cyclosporin A analogue N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
378
4
8

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 508 publications
(401 citation statements)
references
References 43 publications
11
378
4
8
Order By: Relevance
“…The final execution phase involves an ensemble of degradative, post-mortem phenomena, which altogether lead to the phenotypic manifestations of apoptosis. Generally, the morphological and biochemical changes that characterize late-stage apoptosis are independent of the initial stimulus [5,6].…”
Section: Intrinsic and Extrinsic Apoptosis Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…The final execution phase involves an ensemble of degradative, post-mortem phenomena, which altogether lead to the phenotypic manifestations of apoptosis. Generally, the morphological and biochemical changes that characterize late-stage apoptosis are independent of the initial stimulus [5,6].…”
Section: Intrinsic and Extrinsic Apoptosis Pathwaysmentioning
confidence: 99%
“…This has been particularly substantiated by pharmacological and genetic manipulations of the IM-associated matrix protein cyclophilin D (CypD), and of the IM transmembrane protein adenine nucleotide translocase (ANT) [33][34][35]. Indeed, pharmacological inhibitors of these proteins (cyclosporin A for CypD and bongkrekic acid for ANT) are able to prevent cell death, at least in some models of apoptosis (in vitro and in vivo) [5,36]. Interestingly, the viral protein R (Vpr) from human immunodeficiency virus type I (HIV-1) exerts cytotoxic effects by promoting MMP via direct interaction with ANT (as assessed ex vivo, in purified mitochondria and artificial membranes containing ANT) [37][38][39].…”
Section: Mitochondrial Membrane Permeabilizationmentioning
confidence: 99%
“…Thirdly, flavonoids might modulate the mPT believed to be important in apoptotic cell death by either opening a gateway for cytochrome c release from the mitochondria [74,202] or by activating other mitochondrial-related proapoptotic factors such as DIABLO/smac [72,195]. Inhibitors of the mPTP opening like cyclosporin A bind to cyclophilin D which is associated with the adenine nucleotide transporter (ANT), part of the multi protein complex of the mPTP [200], and modulate mitochondrial depolarization [229], cytochrome c translocation [230], and cell death [74,230]. On the contrary, mPTP openers such as the ANT-activator atractyloside trigger mPTP opening, cytochrome c release and apoptosis [229,230].…”
Section: Flavonoids: Neuroprotective Agents In Vivo and In Vitro?mentioning
confidence: 99%
“…Inhibitors of the mPTP opening like cyclosporin A bind to cyclophilin D which is associated with the adenine nucleotide transporter (ANT), part of the multi protein complex of the mPTP [200], and modulate mitochondrial depolarization [229], cytochrome c translocation [230], and cell death [74,230]. On the contrary, mPTP openers such as the ANT-activator atractyloside trigger mPTP opening, cytochrome c release and apoptosis [229,230]. Interestingly, the mPTP possesses a benzodiazepine binding site and the binding of ligands such as PK11195 [36,55] and antagonists like flumazenil [69] have been shown to modulate the mPTP.…”
Section: Flavonoids: Neuroprotective Agents In Vivo and In Vitro?mentioning
confidence: 99%
“…The inhibition of apoptosis by Bcl-2 has been correlated with the inhibition of various biochemical events which occur in apoptotic cells. These include Ca ++ redistribution inside the cell (Ba y et al, 1993;Lam et al, 1994), free radicals metabolisms (Hockenbery et al, 1993) and mitochondrial permeability transition (Zamzami et al, 1996). More recently it was shown that another anti-apoptotic member of the Bcl-2 family, the protein Bcl-XL, was structurally homologous to the pore forming unit of diphtheria toxin and that it had the capacity to form an ion channel in synthetic membranes (Muchmore et al, 1996;Minn et al, 1997).…”
Section: Introductionmentioning
confidence: 99%